Strategi Pemasaran dan Diferensiasi Produk dalam Menghadapi Persaingan Impor: Studi Kasus PT. Soka Cipta Niaga - Firsta Agdies Eka Nugroho; Rika Rismayanti; Ganjar Santika (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The rapid growth of the Muslim population, both in Indonesia and globally, has driven an increasing need for products to support worship, including Muslim socks. PT Soka Cipta Niaga (PT SCN), a producer of Muslim socks under the brand "SOKA", faces the challenge of low brand awareness, where consumers are more familiar with the product as "wudu socks". This research aims to analyze effective marketing strategies for the "SOKA" brand. The research results show that social media-based promotional strategies, such as Twitter, Facebook, and LinkedIn, are able to reach potential consumers more widely. In addition, activities such as bazaars, Muslim seminars, and Collaboration with Hajj and Umrah organizers has proven effective in expanding the market. The momentum of Ramadan and the Hajj season is a strategic time to increase sales.